Mammary Gland Tumor In Cat And Therapeutic Approach: A Case Report - Muhammad Hambal; Rizka Ayuni; Henni Vanda; Mustafa Sabri (The International Journal of Tropical Veterinary and Biomedical Research, 2018)
This report describes a case of mammary gland tumor in a 1-year-old female cat using a mastectomy approach. The tumor was located on dexter side of mammae. Blood analysis showed good condition of the patient and ready for surgery. Mastectomy was conducted to remove the mass, and the tumor size was measured 7x5x4 cm with solid appearance. The cat was given antibiotics to prevent infection, and the wound dried in five days.